Uji Aktivitas Katalitik Hidrodesulfurisasi Campuran Light Gas Oil (LGO) dan Light Diesel Oil (LDO) dengan Katalis CoMo/ Î³-Al2O3 - Ulya, Isnaeni Nurul; Jumaeri, Jumaeri; Wawan, Wawan; Rahayu, Endah Fitriani; Wijayati, Nanik (Indonesian Journal of Chemical Science, 2020)
Diesel oil is a fossil fuel that is the main source of energy consumed excessively which can cause problems in the environment such as air pollution. This study aims to eliminate sulfur type impurities in diesel oil by hydrotreating process, one of which is through the hydrodesulfurization process. In this study studied the catalytic activity of CoMo / Al2O3 in the HDS process of LGO and LDO blends using Reactor Fixed-Bed Pilot-Plant scale. The effect of parameters on the HDS process was studied by varying temperatures of 330oC, 350oC, 370oC and the influence of the Liquid Hourly Space Velocity (LHSV) 1 hour-1, 1.5 hours-1, 2 hours-1. The results showed an increase in HDS activity of up to 99.99% at an increase in temperature of 370oC with LHSV 1 hour-1.CoMo/Î³-Al2O3 catalyst was able to reduce sulfur content at temperatures of 330oC, 350oC, and 370oC with LHSV 1 hour-1 of 16.56 ppm; 3.85 ppm; 3.79 ppm. From all the results of the analysis it can be concluded that the optimum HDS process at a temperature of 370oC and LHSV 1 hour-1. The decrease in sulfur content obtained is in accordance with European country standards (Euro V), where the sulfur diesel oil content is lower than 10 ppm. The catalytic activity of CoMo/Î³-Al2O3 shows that it increases the HDS process and can reduce activation energy by 18.49 Kj/mol.